Exploring post-graduation mobility: A scoping review of international students’ decision-making - Zhao, Boya; Marangell, Samantha; Baik, Chi (Journal of International Students, 2026)
International student mobility has been an important feature of higher education, attracting substantial research attention in recent decades, yet students’ post-graduation mobility remains largely overlooked in literature. Guided by the PRISMA-ScR framework (JBI) and the guidelines by Arksey and O’Malley (2005), this scoping review synthesised data from 65 studies pertaining to factors influencing international students’ post-graduation migratory decisions. Descriptive mapping and thematic analyses revealed six main dimensions of influences: personal, career and employment, societal, connection, policy and political, and cultural factors. The review suggests that students’ decisions are highly contextualised and situational, and go beyond economic considerations of returns on investment. Additionally, the analysis reveals that students’ decisions are consistently evolving, showing fluidity, uncertainty and temporality. This review contributes to a more nuanced understanding of international student mobility and highlights the importance of reframing the theoretical approaches in future research to better reflect the dynamics of international student mobility pathways.